Prediction of extubation failure in preterm infants. Issue 1 (1st January 2002) - Dimitriou, G; Greenough, A; Endo, A; Cherian, S; Rafferty, G F
Abstract : Objective: To identify whether the results of assessment of respiratory muscle strength or respiratory load were better predictors of extubation failure in preterm infants than readily available clinical data. Patients: Thirty six infants, median gestational age 31 (range 25–36) weeks and postnatal age 3 (1–14) days; 13 were < 30 weeks of gestational age. Methods: Respiratory muscle strength was assessed by measurement of maximum inspiratory pressure generated during airway occlusion, and inspiratory load was assessed by measurement of compliance of the respiratory system. Results: Overall, seven infants failed extubation—that is, they required reintubation within 48 hours. These infants were older (p < 0.01), had a lower gestational age (p < 0.01), and generated lower maximum inspiratory pressure (p < 0.05) than the rest of the cohort. Similar results were found in the infants < 30 weeks of gestational age. Overall and in those < 30 weeks of gestational age, gestational age and postnatal age had the largest areas under the receiver operator characteristic curves. Conclusion: In very premature infants, low gestational age and older postnatal age are better predictors of extubation failure than assessment of respiratory muscle strength or respiratory load.